2022
DOI: 10.1002/adfm.202212124
|View full text |Cite
|
Sign up to set email alerts
|

2D MXenes for Fire Retardancy and Fire‐Warning Applications: Promises and Prospects

Abstract: Frequent fire disasters have caused massive impacts to the environment, human beings, and the economy. MXene has recently been intensively researched as potential flame retardants to provide passive fire protection for other materials via its physical barrier and catalyzing carbonization effects. In parallel, MXene has also demonstrated a great promise for creating early fire warning sensors, which is an emerging field that has the potential to provide active fire response through its thermoelectric effect. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 103 publications
(44 citation statements)
references
References 139 publications
0
44
0
Order By: Relevance
“…In another study, MXene sheets and MCA were hybridized via hydrogen bonding, resulting in mechanically strong and highly flame-retardant TPU composites . Tang’s group has extensively studied the enhancement of flame retardancy of polymer nanocomposites using nanomaterials such as graphene, , MXene, , and boron nitride and combined with traditional flame retardants such as ammonium polyphosphate and polyphosphoramide . The authors concluded that combining nanofillers (in particular two-dimensional (2D) materials) with traditional FRs into polymers can improve not only flame retardancy but also retain/enhance mechanical properties of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, MXene sheets and MCA were hybridized via hydrogen bonding, resulting in mechanically strong and highly flame-retardant TPU composites . Tang’s group has extensively studied the enhancement of flame retardancy of polymer nanocomposites using nanomaterials such as graphene, , MXene, , and boron nitride and combined with traditional flame retardants such as ammonium polyphosphate and polyphosphoramide . The authors concluded that combining nanofillers (in particular two-dimensional (2D) materials) with traditional FRs into polymers can improve not only flame retardancy but also retain/enhance mechanical properties of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Unsaturated polyester (UP) is widely used in transportation, building materials, and electrical insulation and has become a valuable engineering resin because of its superior mechanical resistance, excellent electrical insulation, and ease of processing. Since neat UP is flammable, its applications are greatly limited, thus leading to an increasing demand for flame-retardant UP. Incorporating flame-retardant additives into the UP matrix is a convenient way to obtain flame-retardant UP materials. Traditionally, halogenated flame retardants were widely used; however, with an increasing awareness of environmental protection, halogen-free flame retardants have become increasingly popular for UP, including two-dimensional materials, intumescent flame retardants, , and organophosphorus flame retardants. Due to their high efficacy, low toxicity, and good compatibility with the polymer matrix, organophosphorus flame retardants have become viable flame retardants. Zhao et al synthesized a poly­(hydroxyphenyl imino methyl phenol spirocyclic pentaerythritol diphosphonate), and its addition into UP led to a limiting oxygen index (LOI) value of 28.2% and a UL 94 V-0 rating in the resultant flame-retardant UP as well as a sharp decrease in the peak heat release rate (PHRR) by 60%, demonstrating a dramatic enhancement in flame retardancy. Liquid organophosphorus flame retardants have some shortcomings, even though previous studies have shown that they can enhance flame retardancy.…”
Section: Introductionmentioning
confidence: 99%
“…They provide basic building units for nanoscale systems that are easy to assemble. [7,8] Graphene is the most studied among 2D material, [9][10][11] 2D early transition metal carbides, nitrides or carbonitrides is a new class of compounds that were discovered recently by researchers of Drexel University, named as MXenes. [12][13][14] The first MXene reported was Titanium carbide (Ti 3 C 2 ).…”
Section: Introductionmentioning
confidence: 99%